A Critical Overview of Interleukin 32 in Leishmaniases - Ribeiro-Dias, Fátima; Oliveira, Iara Barreto Neves (Frontiers in Immunology, 2022)
Interleukin-32 (IL-32) has several immune regulatory properties, which have driven its investigation in the context of various diseases. IL-32 expression is reported to be induced in the lesions of patients with American tegumentary leishmaniasis (ATL) by the New World Leishmania spp. that are responsible for causing ATL and visceral leishmaniasis (VL). IL-32 expression may elevate the inflammatory process through the induction of pro-inflammatory cytokines and also via mechanisms directed to kill the parasites. The genetic variants of IL-32 might be associated with the resistance or susceptibility to ATL, while different isoforms of IL-32 could be associated with distinct T helper lymphocyte profiles. IL-32 also determines the transcriptional profile in the bone marrow progenitor cells to mediate the trained immunity induced by β-glucan and BCG, thereby contributing to the resistance against Leishmania. IL-32γ is essential for the vitamin D-dependent microbicidal pathway for parasite control. In this context, the present review report briefly discusses the data retrieved from the studies conducted on IL-32 in leishmaniasis in humans and mice to highlight the current challenges to understanding the role of IL-32 in leishmaniasis.